1999
DOI: 10.1046/j.1365-2362.1999.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide diffusion across membrane lungs protects platelets during simulated extracorporeal circulation

Abstract: Transmembranous diffusion of gaseous NO revealed protective effects on platelets by reducing thrombocytopenia/pathia and preserving platelet reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Others have also suggested that platelet activation and the expression of platelet Pselectin are important steps in the formation of PLAs (41,42). Indeed, the present findings support previous studies that inhaled NO can decrease both platelet Pselectin expression and fibrinogen binding to the platelet glycoprotein IIb/IIIa receptor in healthy volunteers and critically ill patients (4,25,43,44). The significant correlation between the inhibition of PLA formation and the inhibition of P-selectin expression found in the present study provides more evidence that inhibition of P-selectin expression mediates inhibition of PLA formation in critically ill patients.…”
Section: Discussionsupporting
confidence: 92%
“…Others have also suggested that platelet activation and the expression of platelet Pselectin are important steps in the formation of PLAs (41,42). Indeed, the present findings support previous studies that inhaled NO can decrease both platelet Pselectin expression and fibrinogen binding to the platelet glycoprotein IIb/IIIa receptor in healthy volunteers and critically ill patients (4,25,43,44). The significant correlation between the inhibition of PLA formation and the inhibition of P-selectin expression found in the present study provides more evidence that inhibition of P-selectin expression mediates inhibition of PLA formation in critically ill patients.…”
Section: Discussionsupporting
confidence: 92%
“…There are many different strategies to locally provide NO for precise PLT inhibition. A simple approach is the delivery of NO via sweep gas [22,23]. The direct generation of NO can also be achieved by surface modification, whereas the NO-donor species (e.g., diazeniumdiolates) are impregnated, blended or covalently incorporated in polymeric scaffolding blood-contacting materials [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have since corroborated this finding by performing similar in vitro experiments. 15 This phenomenon demonstrates the non-thrombogenic effect of NO administered through an active membrane, but as of present this has not been applied clinically because the rest of the ECLS circuitry remains thrombogenic.…”
Section: Mimicking the Endothelium-the Use Of Nitric Oxide (No) To Prmentioning
confidence: 96%